Design of a high fundamental torque single phase double stator brushless DC motor - Raja Othman, Raja Nor Firdaus Kashfi (2013)
Single phase brushless DC motors (BLDC) are adopted for many low cost applications such as in fans, blowers and other domestic appliances. Recently, single phase BLDC motors are used for portable application such as the mechanical chopper, cutter and grinder. The requirement for such type of motor application is high torque density. However, consideration in the qualities of torque waveform is required in determine the torque density. This is because the fundamental torque which shows the average torque should be used as the torque values compare to maximum torque in calculating the torque density. Maximum torque with large distortion of torque waveform which means that high THD value is not acceptable since does not contributes higher average torque. Besides, low THD in torque waveform subject less ripple and vibration on the motor performance. All of this can be derived by properly design magnetic circuit of BLDC motor. Hence, the motivation of this research work is to design a BLDC motor that has high fundamental torque and low THD by improvise its magnetic circuit. Finite Element Analysis (FEA) is used to analyze the magnetic characteristic including the electro-magnetic torque characteristics in this research. For all cases, volume of the permanent magnet is fixed at 400 mm3 per each pole. The coil magnetomotive force is set for 480 AT per pole. Initially, parallel magnetic circuit in typical type BLDC motor is being studied including the flux distribution, air-gap flux density, and torque characteristic with their harmonic components. Then, several magnetic circuit designs in single and double stator are proposed to overcome the limitation of typical type BLDC motor. Further, analysis on the taper parameters that affect the torque characteristics is carried out among proposed magnetic circuit in BLDC motor. Determination for maximum torque (max. Tm), minimum cogging torque (min. Tc),maximum fundamental torque (max. Tf), and minimum total harmonic distortion (min. THD) are used to select the best model for fabrication. Several proposed magnetic circuits of BLDC motor is fabricated and experimentally evaluated. The simulation results from the FEA analysis are verified with the measurement result. For comparative analysis, motor constant square density, G is used. It can be seen that the motor constant square density, G for single stator Typical SS Parallel and SS Series are 5.54 and 8.54, respectively. Meanwhile, motor constant square density, G for double stator DS Parallel, DS Series A and DS Series B are 2.365, 4.24, and 15.0, respectively. Therefore, it shows that double stator type DS Series B is the best choice among all motors that been studied. In conclusions, the research proposed an optimal magnetic circuit configuration that could provide high fundamental torque and low THD. Finally, this thesis provides guidelines, suggestions and proposes better magnetic circuit in designing BLDC motor.